Changes of microbial community structure during the initial stage of biological clogging in horizontal subsurface flow constructed wetlands. (October 2021) - Zhang, Mingzhen; Xu, Dong; Bai, Guoliang; Cao, Taotao; Liu, Wei; Hu, Ze; Chen, Disong; Qiu, Dongru; Wu, Zhenbin
Graphical abstract: Highlights: The implications of micro-organism variation due to the clogging was investigated. The clogging increased some organic matter-metabolizing bacteria's richness. Some functional bacteria significantly varied with the clogging developing. Abstract: The clogging is a universal problem in constructed wetlands, where microorganisms play an essential role. However, the implication of micro-organism variation due to the clogging is not clear. Four horizontal subsurface flow constructed wetlands (HFCWs) were designed and operated to simulate the process of clogging. The wetland treatment performance and microbial community variation were investigated by regularly monitoring. Results showed the substrate filtration rate and the total phosphorous (TP) removal efficiency consistently decreased and the chemical oxygen demand (COD) and total nitrogen (TN) removal efficiency were at the range of 50%-85% and 10–20%, respectively. The sequencing results indicated that the clogging could affect the richness of bacterial community. The bacterial variation could be attributed to the dissolved oxygen decreasing and organic matter accumulation in the initial clogging period. These findings are expected to provide some theoretical reference for developing the biological methods to indicate the initial clogging in constructed wetlands.